Thyroid dysfunction and anaemia in a large population‐based study. (19th January 2016) - M'Rabet‐Bensalah, Khadija; Aubert, Carole E.; Coslovsky, Michael; Collet, Tinh‐Hai; Baumgartner, Christine; den Elzen, Wendy P. J.; Luben, Robert; Angelillo‐Scherrer, Anne; Aujesky, Drahomir; Khaw, Kay‐Tee; Rodondi, Nicolas
Summary: Objective and background: Anaemia and thyroid dysfunction are common and often co‐occur. Current guidelines recommend the assessment of thyroid function in the work‐up of anaemia, although evidence on this association is scarce. Patients and methods: In the 'European Prospective Investigation of Cancer' (EPIC)‐Norfolk population‐based cohort, we aimed to examine the prevalence and type of anaemia (defined as haemoglobin <13 g/dl for men and <12 g/dl for women) according to different thyroid function groups. Results: The mean age of the 8791 participants was 59·4 (SD 9·1) years and 55·2% were women. Thyroid dysfunction was present in 437 (5·0%) and anaemia in 517 (5·9%) participants. After excluding 121 participants with three most common causes of anaemia (chronic kidney disease, inflammation, iron deficiency), anaemia was found in 4·7% of euthyroid participants. Compared with the euthyroid group, the prevalence of anaemia was significantly higher in overt hyperthyroidism (14·6%, P < 0·01), higher with borderline significance in overt hypothyroidism (7·7%, P = 0·05) and not increased in subclinical thyroid dysfunction (5·0% in subclinical hypothyroidism, 3·3% in subclinical hyperthyroidism). Anaemia associated with thyroid dysfunction was mainly normocytic (94·0%), and rarely macrocytic (6·0%). Conclusion: The prevalence of anaemia was higher in overt hyperthyroidism, but not increased in subclinical thyroid dysfunction. Systematic measurement of thyroid‐stimulating hormone in anaemic patients is likely to be useful only after excluding common causes of anaemia.